Pengaruh Kualitas Produk dan Harga Produk Terhadap Loyalitas Konsumen Melalui Kepuasan Konsumen Terhadap Produk Mie Instan “Indomie Goreng” : Studi pada Konsumen Mie Instan “Indomie Goreng” di Warmindo Sarjana UPN - Ririn Putri Anggraeni; Siti Ning Farida (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to understand the impact of product quality and product price on consumer loyalty using consumer satisfaction with consumers of fried Indomie instant noodles at "Warmindo Bachelor UPN". This research uses a quantitative type of research. The research results show that there is an influence of the respect variable on the consumer satisfaction variable. Apart from that, consumer satisfaction has an influence on consumer loyalty.